Education-Based Tourism: An Effort to Increase Environmental Awareness among the Younger Generation - Syahreza, Rayyan Ibrahim; King, Heli; Wang, Jinming (Tourism and Hospitality Research, 2026)
Environmental degradation and unsustainable tourism practices remain critical global challenges, particularly as tourism activities increasingly involve younger generations. Education-based tourism has emerged as a strategic approach to fostering environmental awareness by integrating learning experiences into tourism activities. This study aims to analyze the role of education-based tourism in enhancing environmental awareness among the younger generation through a systematic review of empirical and conceptual studies. The research employed a qualitative literature review design, analyzing peer-reviewed journal articles, conference proceedings, and book chapters related to educational tourism, ecotourism, and environmental education. Data were analyzed using thematic content analysis to identify dominant patterns, outcomes, and challenges associated with education-based tourism initiatives. The results indicate that education-based tourism significantly contributes to improving environmental knowledge, attitudes, and pro-environmental behaviors among young participants through experiential learning, contextual education, and direct interaction with natural and cultural environments. Furthermore, education-based tourism supports sustainable tourism development by strengthening environmental responsibility and community engagement. However, challenges related to program design, target group specificity, and integration into formal education systems persist. This study concludes that education-based tourism is an effective instrument for increasing environmental awareness among the younger generation and recommends the development of structured, context-sensitive, and participatory tourism education programs to maximize long-term impacts.